Rationalisation Plan Of Talam Corporation Berhad And Europlus Berhad - Yoong, Siew Mei (2004)
This paper attempts to shed some light on the alternative way of financial restructuring by studying one of the largest financial restrusturing occured in 2001 - Talam Group of Companies, a property development company in Malaysia, involving nearly RM1.15 billion of debts as at financial year ended 31 january 2002.